THE INFLUENCE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AND COMPENSATION ON EMPLOYEE PERFORMANCE FURNITURE MANUFACTURING INDUSTRY - Fuji Hidayanti; Denuri Isnanda; Ali Komarudin; Noveria Susijawati; Lisa Harry Sulistiowati (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study investigates the impact of organizational citizenship behavior (OCB) and partial or full compensation on employee performance in the furniture manufacturing industry. The research population comprised employees of furniture manufacturing companies in Cirebon. A simple random sampling technique was employed, yielding a total of 57 respondents. Data was collected using questionnaires. Researchers employ normality and multicollinearity tests to verify that the data meets the assumptions for the chosen statistical models. The analysis employed multiple linear regression, a statistical technique that allows researchers to examine how multiple independent variables (X) influence a single dependent variable (Y). The study used statistical tests (coefficient of determination, t-tests, and F-tests) to measure how much employee performance (Y) can be explained by factors like organizational citizenship behavior (OCB) and compensation. Results showed a positive and significant impact (t-count > t-table: OCB = 7.214 > 2.004, Compensation = 6.608 > 2.004) from both factors (F-count > F-table: 33.297 > 3.17). All tests (partial and simultaneous) confirmed significance (sig value < 0.05).